Discovering cessation strategies used successfully by individuals who are in recovery from methamphetamine addiction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatū, New Zealand - Gordon, Yvonne (Massey University, 2019)
Methamphetamine (MA) misuse is a recognized health issue in New Zealand, and there is a lack of appropriate treatment available for individuals who are methamphetamine dependent. This research sought to gain insight from individuals in New Zealand who have experienced MA dependence and now identify as being in recovery, to discover which strategies, approaches or treatment appeared helpful in their recovery. The participants in the research were seven adults who had abstained from methamphetamine for six months or more. Hermeneutical Phenomenological research was conducted through in-depth interviews, which were audiotaped and transcribed before being analysed. The data were analysed using interpretative phenomenological analysis, which has its theoretical origins in phenomenology and hermeneutics. Four themes emerged to describe the lived experience of recovery from methamphetamine misuse: Getting Away, Support, Personal Sources of Strength, and Treatment. Each theme held importance in the participant's recovery from MA and provided insight into their journey in abstaining and being in recovery. This research should provide valuable information for further research to be conducted on this important health issue. The findings may also be used to assist others who want to enter recovery but do not know how, or what may help them.
Keywords: Methamphetamine abuse; Treatment; New Zealand; Drug addicts; Attitudes; Rehabilitation; Recovering addicts; 520304 Health psychology